Genetic variation in storage protein and starch biosynthesis genes reveals key associations with seed composition in pea (Pisum sativum) - Alemu, Admas; Anguluri, Kavitha; Yuan, Bo; Lametsch, René; Hammenhag, Cecilia (Frontiers in Plant Science, 2025)
Understanding the genetic basis of seed storage proteins and starch biosynthesis in pea (Pisum sativum) is critical for breeding programs aimed at enhancing seed quality, functional properties and nutritional value. In this study, we selected 34 genes encoding storage proteins and 21 genes involved in starch synthesis through literature mining and BLAST analysis. Using these genes as references, we sequenced 64 genomic regions associated with storage proteins and starch metabolic enzymes in 100 genetically diverse global pea accessions. In addition, protein and starch content analysis was conducted for these pea accessions. Targeted sequencing of these genes yielded 8,793 genetic variants, of which 2,573 high-quality single nucleotide polymorphism (SNP) markers were retained for further analysis. Protein content of studied accessions ranged from 19.5 to 37.7%, and starch content from 23.8 to 47.3%, highlighting the substantial phenotypic variation. Furthermore, a strong negative correlation (r = –0.71, p < 0.001) was observed between seed wrinkling and starch content consistent with the documented role of genetic variation in starch biosynthesis in determining seed texture. The SNP-based population structure and genetic diversity assessments revealed a complex genetic landscape with no clear clustering by geographical origin or material types. However, dendrograms constructed from principal components derived from SNP markers revealed a clear clustering of accessions according to their protein and starch content, thereby validating the influence of variants in the targeted genes on these traits. Gene-to-phenotype regression analysis identified key genes significantly associated with protein and starch content including legumin, provicilin and starch-branching enzyme. These findings provide valuable insights into the genetic architecture of storage protein and starch biosynthesis in pea and offer a foundation for targeted breeding strategies aimed at improving seed composition and functional properties.